Motivasi Wisatawan Berkunjung Pada Objek Wisata Pantai Ujung Batu Kota Padang - Monalisa; Riesa, Rafidola Mareta; Novadilastri (Jurnal Kajian Pariwisata Dan Perhotelan, 2023)
Indonesian tourism which has many tourist destinations makes foreign tourists and domestic tourists have the motivation to visit them. One of the cities that is a tourist destination for visiting is the city of Padang with one of the attractions, namely the Ujung Batu Beach tourist attraction. This study discusses the motivation of tourists to visit the Ujung Batu Beach tourist attraction in Padang City. The sampling technique used is accidental sampling. The data collection method was carried out by means of a questionnaire which was distributed online via the Google form. The data analysis method used is descriptive quantitative using interval scale. The results showed that the motivation of tourists to visit Ujung Batu Beach, Padang City consisted of 1) Motivation to relate to other people was in the Very Good category, followed by 2) Motivation to meet physical needs was classified as a good category 3) Motivation to know culture was classified as a good category and 4 ) Motivation to obtain status and prestige are both in the good category.